Improvement of Elderly Health Care Voucher Scheme in Hong Kong - Cheryl C.W Ho; Tommy K.C Ng (ACHSM, 2020)
Elderly Health Care Voucher Scheme is a financial support provided by the government to the elderly for having more choices in selecting private primary health care services. It has been launched for more than ten years (including pilot scheme). The success of the voucher depends on its effectiveness so that Hong Kong elderly can benefit from it. The aim of this article is to analyse whether the voucher scheme has achieved its goals and what improvement can be made. The scheme is successful in encouraging the elderly to use private primary care, considering that the participation rate of the scheme is high, and elderly could use private health care services to supplement public health care services. Yet, the amount of the subsidy is insufficient to support the needs of the elderly and the providers of the voucher are not enough for Hong Kong elderly. Also, it is found that private health care services give the old generation an impression of expensiveness and unreliable even with the support of the Health Care Voucher. To improve the Elderly Health Care Voucher Scheme and solve the problems, the government should increase the amount of the voucher, set standards for regular monitoring, cooperate with private health care providers and invite more providers. Ultimately, the elderly would enjoy greater flexibility in choosing medical services in meeting their needs and the scheme can effectively achieve its purpose.